Total Ischemic Time has Prognostic Implications on Short Term Outcome of Primary Percutaneous Coronary Intervention (pPCI) (London Journal of Medical and Health Research, 2024)
Objectives: Primary percutaneous coronary intervention (pPCI) is being increasingly done as the treatment of acute ST elevation myocardial infarction (STEMI). Time until treatment is paramount in the management of STEMI. But the total ischemic time before pPCI how much influencing the outcome is a matter of interest. So we evaluated the influence of total ischemic time on myocardial reperfusion and short term clinical outcome in patients with STEMI treated with primary PCI.Methods: This prospective observational study was conducted from August 2017 to July 2018 in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Forty eight (48) acute STEMI patients were selected by purposive sampling based on inclusion and exclusion criteria dividing into two groups as short total ischemic time in whom pain to pPCI time was
Keywords: enzymes.; Burns; hypertrophic scars; skin grafts; collagenase; recombinant.; Total ischemic time; Primary PCI (pPCI); prognostic implications.